Moral Realism, ‘Gender Ideology’, and Trans+ Rights - Exall, Maria (Heythrop journal, 2025)
Current debate on the validity of an ethical basis for trans+ rights is often expressed as a clash between moral norms based on a biological understanding of sex, and a social and cultural understanding of gender. I will argue a moral realist case for legal and political equality for trans+ people based on objective, universal, and shared values. Such an approach allows us to acknowledge advances in scientific and social theories which question assumed binaries and gendered behaviours, and challenge certain ‘gender ideology’ critiques within the Catholic Church and their use by populist authoritarians of the far-right.